Mazabraud syndrome associated with McCune-Albright syndrome: a case report and review of the literature. - Biazzo, Alessio; Di Bernardo, Andrea; Parafioriti, Antonina; Confalonieri, Norberto (Acta Biomedica Atenei Parmensis, 2017)
Mazabraud syndrome is a very rare benign disorder characterized by the association of monostotic or polyostotic fibrous dysplasia and one or multiple intramuscular myxomas. McCune -Albright syndrome is a rare benign disorder characterized by the association of polyostotic fibrous dysplasia, cafè-au-lait skin pigmentations and endocrine dysfunction, such as precocious puberty, diabetes mellitus, goiter and breast fibroadenomatosis. The association of Mazabraud syndrome and McCune-Albright in the same patient is an anecdotal event. We report the case of a 28-year-old girl with Mazabraud syndrome associated with McCune-Albright syndrome. Our literature review shows that in these patients there is a higher risk of malignant transformation of fibrous dysplasia into osteosarcoma, confirming previous reports. Conversely, no malignant transformation has been reported for myxomas in isolated Mazabraud syndrome or in the association with McCune-Albright syndrome. We conclude that these patients should be scheduled to a close and long-term follow-up.